Impact of Urban Green Spaces on Air Quality in Bangkok - Chakriwat, Suthida (International Journal of Environmental Sciences, 2024)
Purpose: The aim of the study was to investigate the impact of urban green spaces on air quality in Bangkok. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Urban green spaces in Bangkok have been found to significantly reduce air pollutant levels such as nitrogen dioxide (NO2) and particulate matter (PM10 and PM2.5). These green areas mitigate the urban heat island effect and improve overall environmental quality by promoting carbon sequestration and providing natural cooling effects. Integrating green space planning into urban development strategies is crucial for sustaining these benefits and enhancing public health in Bangkok. Unique Contribution to Theory, Practice and Policy: Biophilia hypothesis, ecosystem services framework & urban heat island mitigation theory may be used to anchor future studies on the impact of urban green spaces on air quality in Bangkok. Municipalities should prioritize the strategic placement and maintenance of green infrastructure, considering factors like proximity to sources of pollution and population density. Policies should also prioritize community engagement and education on the benefits of urban green spaces for air quality and public health.